A Quaternion-Driven Deep Learning-Based Novel Approach For Mobile And Locomotive Robot Path Planning And Motion Prediction - Pote, Jamie (My University, 2022)
In this study, I address the locomotive-robot dilemma in movement task sequences. Our method combines geometric motion planning and locomotion prediction using quaternions and deep learning architecture. This is comparable to human motion prediction. I begin by developing a collision-avoidance-based motion planning method. Then, using transformer deep learning, I anticipate robot locomotion. I used simulation to demonstrate my findings.
Keywords: Path Planning; Quaternion; Mobile Robot Step Prediction